2014
DOI: 10.2147/cia.s64766
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cholesterol and cognitive function is homocysteine-dependent

Abstract: IntroductionPrevious studies have identified hyperlipidemia as a potential risk factor for dementia and Alzheimer’s disease. However, studies on cholesterol measured in late-life and cognitive function have been inconsistent. Few studies have explored nonlinear relationships or considered interactions with other biomarker measures.MethodsA cross-sectional sample of 1,889 participants from four rural counties in the People’s Republic of China was included in this analysis. Serum total cholesterol, high-density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…The novel findings of this cross-sectional study provide further support for the role of cholesterol as a disease-modifying factor for cognitive dysfunction within PD (Ferri et al, 2005;Cheng et al, 2014;Cooper et al, 2015), supporting the notion that elevated levels of cholesterol may aggravate the pathophysiology of the disease (Paul et al, 2015(Paul et al, , 2017Jin et al, 2019). Furthermore, the identified sex-specific effect of HDL in relation to cognition suggests the presence of differing mechanisms underlying cognitive decline in males and females with PD.…”
Section: Discussionsupporting
confidence: 74%
“…The novel findings of this cross-sectional study provide further support for the role of cholesterol as a disease-modifying factor for cognitive dysfunction within PD (Ferri et al, 2005;Cheng et al, 2014;Cooper et al, 2015), supporting the notion that elevated levels of cholesterol may aggravate the pathophysiology of the disease (Paul et al, 2015(Paul et al, , 2017Jin et al, 2019). Furthermore, the identified sex-specific effect of HDL in relation to cognition suggests the presence of differing mechanisms underlying cognitive decline in males and females with PD.…”
Section: Discussionsupporting
confidence: 74%
“…Another cross-sectional study in South Korea did not find a significant association between (TC) levels (non-fasting) and cognition function in Alzheimer's disease groups ( 21 ). Two additional cross-sectional studies in Chinese population also reported a non-significant relationship ( 6 , 22 ). However, there are also some studies with different findings.…”
Section: Discussionmentioning
confidence: 94%
“…Another cross-sectional study involving 2,000 community dwellings in eight longevity areas found that higher cholesterol, including TC (OR = 0.73), LDL-C (OR = 0.82), and (HDL-C) (OR = 0.81), was associated with better cognitive function in the oldest old ( 5 ). Furthermore, an inversely U-shaped effect of TC on cognition has been observed in a multicenter study with 1,889 people aged 65 years and over from four rural counties ( 6 ).…”
Section: Introductionmentioning
confidence: 93%
“…Those with MCI and higher initial baseline homocysteine levels demonstrated better cognitive and clinical outcomes (88) and reduced brain atrophy (89). Recent preliminary evidence also suggests that the impact of homocysteine on older-age cognition may be dependent on its interactive effects with cholesterol (90). …”
Section: The Role Of Biomarkers: Indicators Of Mechanismsmentioning
confidence: 99%